Penggunaan Antibiotik Profilaksis Bedah pada Sectio Cesarea di RSUD Arifin Achmad Provinsi Riau - M. Yulis Hamidy; Dina Fauzia; Dimas P. Nugraha; M. Imam Muttaqien (Fakultas Kedokteran Universitas Riau, 2016)
Cesarean section is a high risk operation for the development of surgical site infection. Routine prophylaxis withantibiotic may reduce this risk. Antibiotic administrations in presurgery and postsurgery are widely used to avoid andto treat surgical site infection. The purpose of this study was to evaluate the administration of prophylactic antibioticsfor cesarean section at the Arifin Achmad Hospital, Riau Province. This study included 485 patients who had beenunderwent cesarean section for one year period (January 1st – December 31st 2014). Data were collected using patient’smedical record. The study showed that prophylactic antibiotic was given to 43.7% of the subjects. All of the prophylacticsubjects received seftriaxon as prophylactic antibiotic. About 75.0% antibiotic was given <60 minutes before incision.All of the drugs were administered by intravenous route. It can be concluded that there are some inappropriate use ofprophylactic antibiotics. The greatest inappropriateness is inappopriate duration and indication of prophylacticantibiotic.